Psychological Needs and Resources of the Staff in a Pediatric Neurosurgery Ward: A Phenomenological-Hermeneutic Study - Lanini, Iacopo; Tringali, Debora; Lauro Grotto, Rosapia (Frontiers in Psychology, 2022)
Brain tumors are a common form of solid tumors in children and, unfortunately, they are characterized by a very uncertain prognosis. The treatment of this pathology often includes one or more very invasive surgical procedures, quite often in the very first steps of the treatment. Cases of brain tumors in children represent one of the greatest challenges for health care professionals in the domain of pediatric neurosurgery. This is clearly due to the complexity of the therapeutic plan, but also to the nature of the bond that is established between the child, the parents, and the members of the staff during the often-dramatic initial phase of the illness. In this phenomenologic-hermeneutic study, we explore both the emotional and organizational needs, as well as the available professional and personal resources of the staff in the Neurosurgery ward of the Meyer Children’s Hospital in Florence (Italy). The ward staff, composed by 7 surgeons, a pediatric neuro-oncologist, 12 nurses and 4 auxiliary health care professionals, underwent in-depth interviews that were recorded (with the consensus of the participants). The recordings were then transcribed and submitted to content analysis according to COREQ standards. A complex picture of emotional as well as organizational demands emerged from the data. Shared experiences were pointed out, together with more specific and idiosyncratic contents characteristic of different professional roles. The focus of the present paper is twofold – first we consider the needs that are overtly expressed by the staff and then we discuss the main sources of their motivational drives. We find that the latter are mainly found in the quality of the therapeutic bond that is established with the children and the family members, together with the deep interest in one’s own professional activity and in the effective complementarity and integration of the personal and professional qualities of the staff members within the multidisciplinary caring group.